PERBANDINGAN STRATEGI PENGENDALIAN PERSEDIAAN EOQ, JIT, DAN ROP TERHADAP EFISIENSI BIAYA OPERASIONAL: STUDI LITERATUR BERBASIS PENELITIAN STUDI KASUS TERDAHULU - Rizka Aulia; Gayatri Aprilia; Diah Ayu Lestari; Suci Wulandari (PT. Hasba Edukasi Mandiri, 2025)
Inventory control is a crucial component of operational management, helping maintain a bal-ance between product availability and cost efficiency. As a key element in business activities, inventory plays a strategic role in ensuring smooth production and distribution processes. Effec-tive and efficient inventory management not only helps companies avoid the risk of stockouts or overstocking but also contributes to controlling operational costs and improving performance and customer satisfaction. This study aims to compare three primary inventory control strate-gies Economic Order Quantity (EOQ), Just In Time (JIT), and Reorder Point (ROP) to assess their effectiveness in improving operational cost efficiency. This study uses a comparative liter-ature review based on the results of previous case studies that demonstrated the application of these three methods in various company contexts. The results show that EOQ, JIT, and ROP methods are effective in reducing inventory costs and improving the smoothness of the produc-tion process. All three are capable of improving operational cost efficiency, although the level of effectiveness varies depending on company characteristics.